Impact Of Massive Open Online Course (Mooc) As Best Practice In Indonesia Medan Marelan District Elementary School - Rizka Purnama Sari; Irfan Dahnial (Program Studi Pendidikan Guru Sekolah Dasar, Fakultas Keguruan dan Ilmu Pendidikan, Universitas Muhammadiyah Malang, 2022)
This study aims to determine the response of elementary school students to online learning that was carried out during the Covid-19 pandemic. The study used a limited survey conducted for the elementary school level with a total of 32 respondents (1 class). This survey is directed to find out the impact of student learning in using the Massive Open Online Course (MOOC), in this case, the use of the website which has been developed to compare learning where students freely express their thoughts in written form (not a close-ended option). In this case, the research instrument that was used is in the form of a questionnaire that is used to find out students’ opinions about internet-based learning that they do during the COVID-19 pandemic. The results of the analysis of the 25 statements in the questionnaire were declared valid, all based on data processing with the help of SPSS for Windows version 25.0. The statement in the questionnaire is said to be valid because of the sig < 0.05, then the questionnaire is declared valid and reliable with the t-count result of 0.874 > 0.05. The results of the study describe how the impact of MOOC as the best practice has the potential to affect students’ attitudes, self-confidence, and independence. Research conducted in the classroom shows that learners consciously construct a unique learner culture within MOOCs. By viewing MOOC as a dynamic global social learning culture, we offer a new lens for learning and learning designers to use in developing, delivering, and facilitating MOOC learning.